The potential utility of HKUST-1 for adsorptive removal of benzene vapor from gaseous streams using a denuder versus a packed-bed adsorption system. (1st December 2020) - Anand, Bhaskar; Younis, Sherif A.; Szulejko, Jan E.; Kim, Ki-Hyun; Zhang, Wei
Abstract: The feasibility of various sorption methods has been explored to remove volatile organic compounds from indoor air (e.g., a packed bed-based air filtration system). However, the large space velocity/pressure drop is a common operational challenge associated with the use of a packed-bed adsorber, especially when using fine powdery adsorbent. Accordingly, this research was carried out to evaluate the effectiveness of two contrasting adsorptive removal systems (i.e., denuder vs. packed-bed) using a metal-organic framework (MOF: Hong Kong University of Science and Technology (HKUST-1) as a model adsorbent) as the test media. In the denuder design, HKUST-1 was coated as a thin layer (thickness 90 μm) on the inner wall of a 90 mm length quartz tube (internal diameter ≈ 4 mm) with the help of a polyvinyl alcohol binder. Additionally, an identical quartz tube was prepared with a HKUST-1 packed bed. The potential applicability of the denuder versus packed-bed was evaluated using gaseous benzene (0.1–10 partial pressure) in a N2 inlet stream at near-ambient conditions (298 K and 1 atm). A comparison of the breakthrough volume and adsorption performance data (capacity and partition coefficient) revealed that the packed bed outperformed the denuder design by four to five-fold at all inlet benzene partial pressures (0.1–10 Pa). Better performance was seen in the denuder system when benzene uptake was conducted at high benzene partial pressures (5–10 Pa) rather than at low partial pressure (<5 Pa) in the inlet stream. The evaluation of pressure drop data indicated the efficacy of the denuder over a packed bed in terms of pressure/space velocity drop, especially at a high flow rate (e.g., 330 mL min -1 ). However, in terms of uptake rate and space time yield, the denuder was 25 times less efficient than the packed bed. Graphical abstract: Image 1 Highlights: Packed bed built with fine sorbents like MOFs can suffer from pressure drop issue. A tube diffusion based denuder was built by coating with a thin-film of MOFs. Performance of both denuder and packed bed system made of MOF was tested. The denuder showed no pressure drop for benzene uptake at the expense of efficiency loss.